Finite element simulations of inclined magnetic field and mixed convection in an enclosure with periodically heated walls in the presence of an obstacle - Khan, Y.; Mahmood, Rashid; Majeed, Afraz Hussain; Irshad, Sadia; Alameer, A.; Faraz, N. (Frontiers in Physics, 2022)
Current manifestation is utilized to explicate the inspiration of combined convection flows in a cavity with a square cylinder placed at the center of cavity having coordinates (0.5, 0.5). To be more specific, right and left sided vertical walls are kept cold, and the lower wall is to be heated in uniform and non-uniform manners, while upper horizontal wall is moved with constant velocity and it is thermally adiabatic. The obstacle is treated as cold as well as thermally adiabatic and the no-slip velocity boundary conditions are specified at its surface. A highly efficient numerical technique recognized as finite element method (FEM) with LBB stabilized choice of finite element pair is used to yield the numerical approximations for temperature, velocity and pressure profiles. The non-linear iterations are terminated at residual below 10-6 whereas the inner core linear solver is based on Gaussian elimination with special reordering of unknowns. To show consistency of implemented numerical technique the parametric study is based on the most relevant non-dimensional parameters namely Grashoff number Gr ranging from , the Hartmann number Ha changing from 0 to 50 and the Reynolds number Re varying from 10 to 200. Computations in the forms of velocity streamlines and isotherm contours profiles are adorned.